Implications of Thermodynamic Control: Dynamic Equilibrium Under Ball Mill Grinding Conditions. Issue 11 (19th October 2021) - Belenguer, Ana M.; Lampronti, Giulio I.; Sanders, Jeremy K. M.
Abstract: We report a powerful example of subtle dynamic equilibrium control under milling conditions using the base catalysed solid state disulfide exchange reaction between two homodimers (bis‐2‐nitrophenyldisulfide and bis‐4‐nitrophenyldisulfide) to produce the heterodimer (4‐nitrophenyl‐2‐nitrophenyl‐disulfide). Under ball mill neat grinding conditions, the equilibrium is reproducibly represented by homodimers and Form A of the heterodimer in a molar ratio of 1 to 4. The heterodimer crystallizes in two different polymorphic forms, Form A and Form B, which can be interconverted by changing the milling conditions between neat grinding and liquid assisted grinding with a number of solvents. Because such milling equilibria are reversible and dynamic in nature, we interpret these end points as existing in local thermodynamic wells. Moreover, homodimer bis‐2‐nitrophenyldisulfide also shows two polymorphs, Form I and Form II, depending on the milling conditions, further complicating the picture. Because of the nanocrystalline nature of these solid forms, we suggest that surface effects are responsible for the switch in polymorph stabilities in the milling jar. Abstract :